Zad1.
a)3x+34=-2x-11
b)4x-5-7x=2-5x-23
c)4x-5+2x=4-7x+31
d)3x-15>5x-33
e)5x-7≥8x+11
f)6x+7-7x>2-4x-17
g)-4x-11+3x≤3-2x-24
Zad2
a.(x+4)-2(x+3)=7
b)-(3-x)+(2x+2)=-(1-2x)+(2x-15)
Zad3.
a)-3(x+2)-2(x+3)=7
b)2(2x+5)-3(5+x)=4(x+3)+2(2x+2)
c)4(2x-8)-6(x-4)=2


Pomocy potrzebne na jutro..!!

3

Odpowiedzi

2010-04-07T17:45:10+02:00
Zad1.
a)3x+34=-2x-11
5x=-45
X=-9

b)4x-5-7x=2-5x-23
2x=-16
X=-8

c)4x-5+2x=4-7x+31
13x=40
X=40/13

d)3x-15>5x-33
-2x>-18
X>9

e)5x-7≥8x+11
-3 x>=18
x>=-6

f)6x+7-7x>2-4x-17
3x>-22
x>-22/3

g)-4x-11+3x≤3-2x-24
x<=-10

Zad2
a.(x+4)-2(x+3)=7
x+4-2x-6=7
-x=9
X=-9

b)-(3-x)+(2x+2)=-(1-2x)+(2x-15)
-3+x+2x+2=-1+2x+2x-15
-x=-15
X=15

Zad3.
a)-3(x+2)-2(x+3)=7
-3x-6-2x-6=7
-5x=19
X=-19/5

b)2(2x+5)-3(5+x)=4(x+3)+2(2x+2)
4x+10-15-3x=4x+12+4x+4
-7x=21
X=-3

c)4(2x-8)-6(x-4)=2
8x-32-6x+24=2
2x=10
X=5
2010-04-07T17:54:07+02:00
1)
a)3x+34=-2x-11
3x+2x=-11-34
5x=-45
x=-9

b)4x-5-7x=2-5x-23
4x-7x+5x=2-23+5
2x=-16
x=-8

c)4x-5+2x=4-7x+31
4x+2x+7x=4+31+5
13x=40
x=40/13
x=3,08 (w przybliżeniu)

d)3x-15>5x-33
3x-5x>-33+15
-2x>-18
x>9

e)5x-7≥8x+11
5x-8x≥11+7
-3x≥18
x≥-6

f)6x+7-7x>2-4x-17
6x-7x+4x>2-17-7
3x>-22
x>-22/3
x>-7⅓

g)-4x-11+3x≤3-2x-24
-4x+3x+2x≤3-24+11
x≤-10

2)
a.(x+4)-2(x+3)=7
x+4-2x-6=7
x-2x=7+6-4
-x=9
x=-9

b)-(3-x)+(2x+2)=-(1-2x)+(2x-15)
-3+x+2x+2=-1+2x+2x-15
x+2x-2x-2x=-1-15+3-2
-x=-15
x=15

3)
a)-3(x+2)-2(x+3)=7
-3x-6-2x-6=7
-3x-2x=7+6+6
-5x=19
x=-19/5
x=-3,8

b)2(2x+5)-3(5+x)=4(x+3)+2(2x+2)
4x+10-15-3x=4x+12+4x+4
4x-3x-4x-4x=12+4-10+15
-7x=21
x=-3

c)4(2x-8)-6(x-4)=2
8x-32-6x+24=2
8x-6x=2-24+32
2x=10
x=5
2010-04-07T17:56:21+02:00
Zad.1

a)3x+34=-2x-11
3x+2x=-11-34
5x=-45/:5
x=-9

b)4x-5-7x=2-5x-23
4x-7x+5x=2-23+5
2x=-16/:2
x=-8

c)4x-5+2x=4-7x+31
4x+2x+7x=4+31+5
15x=40/:15
x=2²/₃

d)3x-15>5x-33
3x-5x>-33+15
-2x>-18/:(-2)
x<8

e)5x-7≥8x+11
5x-8x≥11+7
-3x ≥ 18/:(-3)
x ≤ -6

f)6x+7-7x>2-4x-17
6x-7x+4x>2-17-7
3x>-22/:3
x>-7⅓

g)-4x-11+3x≤3-2x-24
-4x+3x+2x≤3-24+11
x≤-10

Zad.2

a.(x+4)-2(x+3)=7
x+4-2x-6=7
x-2x=7-4+6
-x=3/:(-1)
x=-3

b)-(3-x)+(2x+2)=-(1-2x)+(2x-15)
-3+x+2x+2=-1+2x+2x-15
x+2x-2x-2x=-1-15+3-2
-x=-15/:(-1)
x=15

Zad.3
a)-3(x+2)-2(x+3)=7
-3x-6-2x-6=7
-3x-2x=7+6+6
-5x=19/:(-5)
x=-3⁴/₅

b)2(2x+5)-3(5+x)=4(x+3)+2(2x+2)
4x+10-15-3x=4x+12+4x+4
4x-3x-4x-4x=12+4-10+15
-7x=21/:(-7)
x=-3

c)4(2x-8)-6(x-4)=2
8x-32-6x+24=2
8x-6x=2+32-24
2x=10/:2
x=5
1 5 1